Image of the Family in Polish and French Books for Children - Kwiatkowska, Agnieszka (Porównania, 2023)
Family is an important topic in literature for children and youth. In works for the youngest readers, it is presented differently than in texts for older children and youth—as a safe environment that offers acceptance. The specificity of the image of the family in Polish literature for children has been illustrated in this article by comparing it with French books for children. French books usually operate with a plot and combine the informational character with artistic values. The diversity experienced in the spirit of freedom, equality and fraternity is shown in them as a richness and a source of joy. Polish books emphasize the value of the family, but they are devoid of the lightness and playfulness present in French texts. The diverse image of the family presented in books with informational content is to a small extent reflected in literary texts.